Relationship between Job Demands‐Resources and turnover intention in chronic disease – The example of multiple sclerosis. (27th April 2021) - Lehmann, Anja I.; Rodgers, Stephanie; Calabrese, Pasquale; Kamm, Christian P.; Wyl, Viktor von; Bauer, Georg F
Abstract: Considering the Job Demands‐Resources (JD‐R) model, this study investigated the relation between job demands, job resources and turnover intention among persons with multiple sclerosis (pwMS) as an example of chronic disease. We hypothesized that job demands and job resources are related to turnover intention, as mediated by work engagement, burnout, and MS‐related work difficulties. Moreover, we assumed that MS‐related work difficulties mediate the relationship between job demands/job resources and burnout and between job resources and work engagement. Using cross‐sectional data ( N  = 360) of pwMS from the Swiss MS Registry, structural equation modelling was applied. The results confirm the JD‐R model can be related to turnover intention among pwMS. Moreover, MS‐related work difficulties mediated the relationship between job demands and burnout, between job resources and work engagement, and between job resources and burnout. The findings suggest that there may be benefit in applying and adapting the JD‐R model for people with a chronic disease such as MS. This group of people might benefit from the promotion of job resources and a reduction in job demands, leading to changes in work engagement, burnout, and MS‐related work difficulties and thus to an increased likelihood to stay at work.